Terapi Komplementer Pada Asma: Literature Review - Lilyana, Maria Theresia Arie (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2022)
Bronchial asthma is a reversible narrowing of the bronchi due to bronchial hyperactivity. Repeated asthma attacks with mild or severe degrees turned out to have a negative impact on the sufferer and became a cause of death. Routine therapy given during asthma exacerbations is expected to prevent the severity of acid attacks when they occur. Complementary therapies that exist today are expected to have a positive impact when an asthma attack occurs. Methods: The writing of this article uses the literature review method to find complementary therapies that can be given to asthma patients. Results: Traditional eastern medicine states that asthma attacks occur due to weakness of the lung meridians, Discussion: weakness that occurs in the lung meridians can be improved by increasing Qi (energy) through herbs, strengthening the lung meridians using acupuncture. Conclusion: Complementary therapy can be applied appropriately and carefully once we are able to establish a diagnosis based on TCM treatment of excess or defensive lung meridians.